Buckling Analysis of Unidirectional Polymer Matrix Composite Plates - Uleiwi, Dr. Jawad Kadhim (Al-Khwarizmi Engineering Journal, 2017)
This study deals with the estimation of critical load of unidirectional polymer matrix composite plates by using experimental and finite element techniques at different fiber angles and fiber volume fraction of the composite plate. Buckling analysis illustrated that the critical load decreases in nonlinear relationship with the increase of the fiber angle and that it increases with the increase of the fiber volume fraction. The results show that the maximum value of the critical load is (629.54 N/m) at (q = 0°) and (Vf = 40 %) for the finite element method, while the minimum value of the critical load is (49 N/m) at (q = 90°) and (Vf = 10 %) for the experimental results. The results also indicated that the maximum difference between the finite element analysis and experimental work is about (11 % ) at ( q = 0°) and (Vf = 40 %).